2023
DOI: 10.1111/prd.12501
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus‐Bacteria pathogenic interaction in juvenile (aggressive) periodontitis. A novel etiologic concept of the disease

Abstract: Localized juvenile (aggressive) periodontitis starts at puberty in otherwise healthy individuals and involves the proximal surfaces of permanent incisors and first molars. The disease destroys a sizeable amount of periodontal bone within a few months despite minimal dental plaque and gingival tissue inflammation. Cytomegalovirus and Epstein–Barr virus, as well as the two main periodontopathic bacteria Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis, are linked to juvenile periodontitis. Juve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…The present results, obtained with established clinical criteria and microbiological methods in a study population with a high Ag/MI periodontitis prevalence, and including a periodontal healthy control group, are valid and relevant today in confirming and extending previous data on the prevalence and subgingival microbiota of Ag/MI periodontitis 5–13,35–41 …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The present results, obtained with established clinical criteria and microbiological methods in a study population with a high Ag/MI periodontitis prevalence, and including a periodontal healthy control group, are valid and relevant today in confirming and extending previous data on the prevalence and subgingival microbiota of Ag/MI periodontitis 5–13,35–41 …”
Section: Discussionsupporting
confidence: 86%
“…Importantly, bacterial pathogens alone may not comprise the complete pathoetiology of Ag/MI periodontitis, as detailed in a recent paper 13 . For example, some young individuals harboring subgingival A. actinomycetemcomitans or P. gingivalis do not develop localized Ag/MI periodontitis, and some periodontal sites in localized Ag/MI periodontitis patients contain A. actinomycetemcomitans or P. gingivalis without experiencing significant periodontal breakdown 13 . The Ag/MI periodontitis and healthy periodontal groups in the current study may have shown similar findings with microbiological examination of more study sites in each group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, periodontitis patients with elevated subgingival temperatures plus high levels of P. gingivalis or Campylobacter rectus showed significantly more disease‐active sites than patients with a combination of cool subgingival temperature and low periodontal pathogen levels (Haffajee et al, 1991 ). Since severe herpesvirus infection, like bacterial pathogens, is more prominent in disease‐active than in disease‐stable periodontitis sites (Kamma et al, 2001 ; Slots et al, 2003 ), and usually coexist with major periodontopathic bacteria (Chen et al, 2020 ; Slots & Rams, 2023 ), hot periodontal sites are also anticipated to harbor high herpesvirus copy counts with increased risk for periodontal breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis patients typically receive conventional (mechanical) therapy which may not always control the extraordinarily complex mixture of pathogenic bacteria and active herpesviruses existing within deep periodontal pockets, narrow furcation sites, and inflamed gingiva (Rams & Slots, 2023 ). Also, because the initial onset of periodontal breakdown tends to induce major tissue destruction (Slots & Rams, 2023 ), periodontics may preferably employ preemptive therapy which uses clinical and/or laboratory tests to identify high‐risk patients and guide effective treatment before impending disease progression.…”
Section: Introductionmentioning
confidence: 99%